Metadados como elementos do processo de catalogação - Alves, Rachel Cristina Vesú [UNESP] (2010)
The 21 st century has been marked by related changes to information and technology, notably as regards the production and use of information in the computing technologies and in the development of information and communication technologies (ICTs) to disseminate them. Thus, the representation of information has become requirement in many areas of knowledge and to meet this need were developed metadata standards that diversify from simple structures, through a kind of intermediate standard to more complex structures description. The diversity of standards Information Science area is faced with the following impasse that constitutes a research problem: how to construct appropriate and standardized representations to ensure unity and efficient retrieval of information resources? This research which belongs to information and technology line has as theme the analysis of forms of representation of information resources, in view of the changes caused by advances in ICTs in the descriptive treatment of information (DTI) with the emergence of metadata. The focus is on analysis of the theories, principles, fundamentals and tools that guide of the standardized representations development in the Information Science field. The thesis hold for this research is that the strategic integration between computing technologies and methods used in descriptive treatment of information (DTI) processes of the Science Information field consolidate the consistent and standardized construction of metadata providing a representation which ensures the unity and resources retrieval in digital information environments different. Thus, the research hypothesis is that the theories, principles, fundamentals, methods and techniques of cataloging, which are currently going through technological changes, are methodologies that guide the standardized... (Complete abstract click electronic access below)